APEXIFICATION OF A TOOTH WITH DENS INVAGINATUS (A CASE REPORT) - Epita Sarah Pane (Faculty of Dentistry, Universitas Indonesia, 2015)
Dens invaginatus is a developmental malformation of teeth. A successful treatment of a maxillary lateral with dens invaginatus extending to mid root area, incomplete apical closure and large apical radiolucency will be presented. Sixteen months apexification with calcium hydroxide dressing was effective in resolving the problem after ultrasonic debridement, sodium hypochlorite irrigation. A 6-month recall radiograph is presented showing successful healing of the periapical lesion. Conventional endodontic treatment with calcium hydroxide apexification showed a favourable healing and will enhance the prognosis of the tooth.